Plant Secondary Metabolite Biosynthesis and Transcriptional Regulation in Response to Biotic and Abiotic Stress Conditions - Jan, Rahmatullah; Asaf, Sajjad; Numan, Muhammad; Lubna; Kim, Kyung-Min (Agronomy (Basel), 2021)
Plant secondary metabolites (SMs) play important roles in plant survival and in creating ecological connections between other species. In addition to providing a variety of valuable natural products, secondary metabolites help protect plants against pathogenic attacks and environmental stresses. Given their sessile nature, plants must protect themselves from such situations through accumulation of these bioactive compounds. Indeed, secondary metabolites act as herbivore deterrents, barriers against pathogen invasion, and mitigators of oxidative stress. The accumulation of SMs are highly dependent on environmental factors such as light, temperature, soil water, soil fertility, and salinity. For most plants, a change in an individual environmental factor can alter the content of secondary metabolites even if other factors remain constant. In this review, we focus on how individual environmental factors affect the accumulation of secondary metabolites in plants during both biotic and abiotic stress conditions. Furthermore, we discuss the application of abiotic and biotic elicitors in culture systems as well as their stimulating effects on the accumulation of secondary metabolites. Specifically, we discuss the shikimate pathway and the aromatic amino acids produced in this pathway, which are the precursors of a range of secondary metabolites including terpenoids, alkaloids, and sulfur- and nitrogen-containing compounds. We also detail how the biosynthesis of important metabolites is altered by several genes related to secondary metabolite biosynthesis pathways. Genes responsible for secondary metabolite biosynthesis in various plant species during stress conditions are regulated by transcriptional factors such as WRKY, MYB, AP2/ERF, bZIP, bHLH, and NAC, which are also discussed here.